Effect of the introduction of immediate judge's decisions in 2018 on the use of coercive measures in psychiatric hospitals in Germany: a population-based study - Erich Flammer; Sophie Hirsch; Tilman Steinert (Elsevier, 2021)
Background: On 23 July 2018, the German Constitutional Court decided that mechanical restraint in psychiatric patients lasting longer than 30 minutes requires a judge's immediate decision. On the same day, the German Association for Psychiatry and Psychotherapy published its guideline on the prevention of coercion and violence. The registry for coercive measures in the federal state of Baden-Wuerttemberg, available since 2015 and comprising all 32 hospitals licensed to admit involuntary patients, has made it possible to evaluate the effect of the legal change, considered the strongest intervention ever in Germany to reduce coercion. Methods: We analysed the mean percentage of patients subjected to coercive measures and the mean cumulative duration of these interventions in ICD-10 diagnostic groups in psychiatric hospitals from 2017 compared to 2019 among a total of 233,0273 admissions. Findings: The percentage of patients subjected to any kind of freedom-restricting coercion decreased from 6·6% in 2017 to 5·8% in 2019 (p = 0·000). Accordingly, the percentage of patients subjected to mechanical restraint decreased from 4·8% to 3·6% in 2019 (p = 0·000). At the same time, the percentage of patients subjected to seclusion increased from 2·9% to 3·3% (p = 0·000). The median cumulated duration of restraint and seclusion per affected case decreased from 12·5 to 11·9 hrs (p = 0·001). Interpretation: There is clear evidence that a strong legal intervention was effective in reducing the use of coercive measures under routine conditions. Funding: The registry is funded by the Ministry of Social Welfare and Integration.